The mechanics of rubber-to-metal bond failure - Ansarifar M A; Lake G J (Journal of Adhesion, 1995)
In many applications, rubber is bonded to metal for fixing purposes or to alter the stiffness. Integrity of the bond is often vital to maintain the required stiffness characteristics and ensure adequate life. The mechanics of bond failure is being studied for various types of deformation. Provided that tests are carried out under suitable loading conditions, time-dependent failure with a similar locus has been observed in peeling at 90 or 180 , pure shear and various combinations of simple shear and compression. There are indications that an energetics approach can enable results from different geometries to be quantitatively interrelated. Cavitation-like processes observed in the rubber in the bond region are belived to result from the constraint imposed by the metal and may be the cause of the time-dependent failure
Source Year: 1996
Keywords: Metal bonding; Rubber